Readiness of the Bureaucratic Apparatus and Its Influence on Services for Online-Based Socio-Economic Community Development Programs in Tebing Tinggi City - Manda Yulian; Sirojuzilam; Suwardi Lubis; Agus Purwoko (International Journal of Architecture and Urbanism, 2026)
Online-based bureaucratic services have become a strategic instrument for improving the accessibility, speed, transparency, and accountability of local government services. In Tebing Tinggi City, digital service initiatives have been introduced by several public institutions, yet their success depends on the readiness of the bureaucratic apparatus responsible for operating and maintaining these systems. This study examines the level of apparatus readiness and analyzes its influence on socio-economic community development program services. A quantitative approach was employed through descriptive and explanatory analysis. Data were collected using questionnaires administered to 253 government officials involved in public service delivery. Apparatus readiness was assessed through understanding or insight, technology mastery, mental development, moral development, formal education, informal education, and material incentives. The findings show that apparatus readiness is generally within the moderate to high category. Regression analysis confirms that readiness variables simultaneously have a significant effect on socio-economic development service performance. Partially, technology mastery, moral development, and material incentives exert significant positive effects, whereas understanding or insight, mental development, and formal education do not show significant partial effects. The study highlights the need to strengthen digital competence, ethical commitment, and performance-based incentive systems to improve online public service delivery and support urban socio-economic development programs